2015
DOI: 10.5455/ijmsph.2015.1411201483
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus 2 infection in HIV-seropositive individuals in Tamil Nadu, India

Abstract: Background: Viral infection with Herpes Simplex Virus (HSV) is one of the most common opportunistic infections in seropositive patients of Human Immunodeficiency Virus (HIV). Studies have confirmed that genital herpes caused by HSV-2 has been associated with two-to threefold increased risk of HIV acquisition.Objective: To determine the seroprevalence of HSV-2 in HIV-positive patients.Materials and Methods: A prospective, cross-sectional study was conducted from July 2012 to January 2013 and HIV-positive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This finding is in contrary to the findings of Jacob et al, Anuradha et al who reported more seropositivity among women than men. 23,15 This is explained by more of the participants in the study were men. Studies conducted globally have reported similar and more prevalence of HSV-2 seropositivity ranging from 6% in general population and 50% in high-risk groups.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in contrary to the findings of Jacob et al, Anuradha et al who reported more seropositivity among women than men. 23,15 This is explained by more of the participants in the study were men. Studies conducted globally have reported similar and more prevalence of HSV-2 seropositivity ranging from 6% in general population and 50% in high-risk groups.…”
Section: Discussionmentioning
confidence: 98%